Histopathological analysis of duragen collagen matrix over time in humans - Takuma Maeda; Kaima Suzuki; Peyton L. Nisson; Yoshiki Mochizuki; Reina Mizuno; Akio Teranishi; Yushiro Take; Tomomichi Kayahara; Hiroki Kurita (Scientific Reports)
Abstract DuraGen is a widely used type I collagen matrix derived from bovine Achilles tendon that promotes fibroblast ingrowth and neovascularization. However, it remains unknown the time required for dura regeneration and reabsorption of the graft. We evaluate the histopathological characteristics of implanted DuraGen in humans across multiple time points. Patients who underwent a decompressive craniectomy and duraplasty with DuraGen at our institution between January 2020 and September 2021 were prospectively enrolled. At the time of the subsequent surgery, including cranioplasty, DuraGen and associated tissues removed from patients were sent for histopathological analysis. For each patient, time from index surgery to subsequent surgery was categorized into three groups: early (0–20 days), intermediate (21–30 days), and late (> 30 days). Baseline characteristics, primary disease, operative time, complication rate, and histopathological findings were compared between groups. A total of 28 patients were enrolled in the study. Seven specimens (25.0%) were collected within 20 days after craniectomy, 9 specimens (35.7%) between 21 and 30 days, and 12 specimens (39.3%) over 31 days. Histopathologically, implanted collagen matrix, erythrocyte infiltration, and fibrin layer decreased over time, whereas fibroblasts and endogenous collagen increased. Receiver operating characteristic analysis showed that the cut-off time post-implantation for presence of endogenous collagen was 34 days after DuraGen implantation (area under the curve = 0.810). We found that DuraGen was replaced by fibroblast-derived endogenous collagen as early as 34 days post-implantation. Although certain findings remain to be further validated, the present study substantiates DuraGen as a reliable substitute, with findings derived from clinical outcomes and histopathological changes.